2021
DOI: 10.1128/msystems.00300-21
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities in a Serpentinizing Aquifer Are Assembled through Strong Concurrent Dispersal Limitation and Selection

Abstract: Microbial communities existing under extreme or stressful conditions have long been thought to be structured primarily by deterministic processes. The application of macroecology theory and modeling to microbial communities in recent years has spurred assessment of assembly processes in microbial communities, revealing that both stochastic and deterministic processes are at play to different extents within natural environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…Indeed, there are active microbial ecosystems in the deep subsurface fueled by serpentinization (reviewed previously in Schrenk et al, 2013 ). The origin of microorganisms within these subsurface communities is thought to be related to transportation to the subsurface during ophiolite obduction or introduction from groundwater along slow regional flow pathways ( Sabuda et al, 2020 ; Putman et al, 2021 ). Microbial communities dependent on serpentinization are of particular interest to theories of the origin of life and potential life elsewhere in the solar system such as Mars or icy moons (e.g., Schulte et al, 2006 ; Martin et al, 2008 ; Cardace and Hoehler, 2009 ; Sojo et al, 2016 ; Preiner et al, 2018 ; Cartwright and Russell, 2019 ; Russell and Ponce, 2020 ; Taubner et al, 2020 ).…”
Section: Exploring the Terrestrial Deep Biospherementioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, there are active microbial ecosystems in the deep subsurface fueled by serpentinization (reviewed previously in Schrenk et al, 2013 ). The origin of microorganisms within these subsurface communities is thought to be related to transportation to the subsurface during ophiolite obduction or introduction from groundwater along slow regional flow pathways ( Sabuda et al, 2020 ; Putman et al, 2021 ). Microbial communities dependent on serpentinization are of particular interest to theories of the origin of life and potential life elsewhere in the solar system such as Mars or icy moons (e.g., Schulte et al, 2006 ; Martin et al, 2008 ; Cardace and Hoehler, 2009 ; Sojo et al, 2016 ; Preiner et al, 2018 ; Cartwright and Russell, 2019 ; Russell and Ponce, 2020 ; Taubner et al, 2020 ).…”
Section: Exploring the Terrestrial Deep Biospherementioning
confidence: 99%
“…Recent work utilizes next generation DNA sequencing for taxonomic and functional classification of borehole fluids in combination with other techniques such as microcosm or enrichment based experiments ( Crespo-Medina et al, 2014 ; Meyer-Dombard et al, 2018 ; Fones et al, 2021 ; Glombitza et al, 2021 ), stable isotope analyses ( Nothaft et al, 2021a , b ), radioisotope labeling ( Fones et al, 2021 ; Glombitza et al, 2021 ; Templeton et al, 2021 ), and ecological/hydrological modeling ( Putman et al, 2021 ). Transcriptomic and single cell genomics studies have also shown mechanisms of adaptation of microbial life to serpentinizing environments ( Fones et al, 2019 , 2021 ; Merino et al, 2020 ; Kraus et al, 2021 ).…”
Section: Exploring the Terrestrial Deep Biospherementioning
confidence: 99%
See 3 more Smart Citations